An alternative CTCF isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis - Jiao Li (Nature Portfolio, 2019)
CTCF plays key roles in gene regulation, chromatin insulation and organizing the higher-order chromatin architecture of mammalian genomes. Here the authors investigate the function an alternatively spliced shorter CTCF isoform, finding that this isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis.